2019
DOI: 10.1111/codi.14794
|View full text |Cite
|
Sign up to set email alerts
|

Selective central vascular ligation (D3 lymphadenectomy) in patients undergoing minimally invasive complete mesocolic excision for colon cancer: optimizing the risk–benefit equation

Abstract: AimComplete mesocolic excision (CME) with central vascular ligation (CVL) has been advocated for right colon adenocarcinoma (RC), but the radicality of vascular dissection remains controversial. Our aim is to report outcomes of selective CVL (D3 lymphadenectomy) during minimally invasive CME for RC.MethodA prospective database identified patients who were treated for RC between 2009 and 2016. Minimally invasive CME was standard. The radicality of lymphadenectomy was defined as high ligation (HL) versus CVL bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
0
33
0
2
Order By: Relevance
“…A total of 19 publications met the inclusion criteria, and these were included in the final analysis ( Table 1). [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] There was a total of 25 688 patients who underwent surgery for colorectal cancer, who were dichotomised into two groups; patients who underwent CME, and those who underwent traditional colectomy. A total of 14 431 patients (56.2%) underwent CME.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 19 publications met the inclusion criteria, and these were included in the final analysis ( Table 1). [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] There was a total of 25 688 patients who underwent surgery for colorectal cancer, who were dichotomised into two groups; patients who underwent CME, and those who underwent traditional colectomy. A total of 14 431 patients (56.2%) underwent CME.…”
Section: Resultsmentioning
confidence: 99%
“…In one study with 45 patients, there were no instances of local recurrence, and another study had just one patient with local recurrence among a pool of 56 patients. 4,16 There was a significant difference between lymph node yield between the two groups with an SMD of 1.31 favouring CME (95% CI 0.66-1.95, P < 0.001) (Appendix S1). There were no significant differences between the two groups in terms of pooled 3-year DFS (RR 0.92, 95% CI 0.82-1.04, P = 0.174), 5-year DFS (RR 0.99, 95% CI 0.90-1.09, P = 0.827), and overall mortality (OR 1.19, 95% CI 0.86-1.66, P = 0.335), but pooled 5-year OS was significantly higher in the CME group (RR 0.82, 95% CI 0.77-0.87, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of CME has been adopted for many years with solid evidence and strong support by more and more surgeons as the optimal approach for colon cancer surgery [11][12] . It is reported that central nodal metastases occurs in up to 11% of cases (usually range from 0 to 5.8%) [13][14] . Therefore, CME with central vascular ligation (CVL) was thought to be potentially successful in removing lymph node metastases and avoiding vascular and neural invasion in the entire regional draining area.…”
Section: Discussionmentioning
confidence: 99%
“…Following the SMV-first approach principles provides a safe plane for dissection, and, in conjunction with ICG, facilitates the delineation of the vascular anatomy, to enable robotic salvage surgery to be performed. [1][2][3] FUNDING No sources of support.…”
mentioning
confidence: 99%